PENGEMBANGAN SISTEM PENILAIAN KINERJA PARAMEDIS DENGAN BALANCED SCORECARD BERDASARKAN REAL DOCUMENTS - Wiji Setiyaningsih (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Previous research has been done on the management system performance appraisal Hospital paramedics at XYZ using a balanced scorecard method to produce effective research paramedic performance assessment, which is supported by the file supporting documents that have been legalized officials authorized online, and the assessment is objective. However, there are still weaknesses in these systems, the automated system has not been able to calculate the value of the amount of any aspect of the assessment is based on real documents entered. As for suggestions to sustainability research for the development of paramedic performance appraisal management system that input data is actually real data with complete information that is able to automatically calculate the value of the amount of each aspect. Based, then the development of management system performance appraisal paramedics at the Hospital XYZ is based on real documents by applying balanced scorecard, so it can streamline employee performance evaluation, with calculation of the value of each aspect (record count) automatically based on the facts of real data documents ,